Corporate entrepreneurship of emerging market firms: Current research and future directions - Irem Demirkan; Qin Yang; Crystal X. Jiang (New England Journal of Entrepreneurship (NEJE), 2019)
Purpose The purpose of this paper is to examine the current state of corporate entrepreneurship (CE) of emerging market firms (EMFs) and provide direction for future research on the topic. Design/methodology/approach The authors specifically review the recent literature between the years 2000 and 2019 on CE with the keywords "corporate entrepreneurship," "emerging economies" and "emerging countries" published in the Australian Business Deans Council list journals. The authors review the existing literature about CE in emerging markets, summarize current achievements and present an agenda for future research. Findings Based on the review, the authors categorized the macro and micro contexts of CE and summarized the current articles on CE in emerging markets within each macro and micro context. The authors conclude that despite the abundance of research on CE that investigates the three prongs of CE in terms of innovation, strategic renewal and new venturing in developed market contexts, there is a scarcity of literature that focuses on CE in emerging markets from a holistic perspective. Originality/value While there is an abundance of literature review on CE in general in terms of the drivers of the construct, the contexts contributing to it and the outcomes, the reviews are lacking about CE specifically within the context of emerging markets. Emerging markets vary from developed markets institutionally, economically, culturally, socially and technologically. However, the questions of how these differences impact the CE activities, as it relates to innovation, venturing and strategic renewal in EMFs, and how these differences provide incentives or hinder the activities that contribute to CE remain mostly unanswered. This paper reviewed the research on CE and emerging market contexts from 2000 to present. It targets to provide a better understanding of the current achievement on this topic and what to be done in the future.
Keywords: 650; Corporate entrepreneurship; Emerging economies; Review; Organizational characteristics; Emerging market firms; Governments